If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2g + 4 Reorder the terms: 10 = 4 + 2g Solving 10 = 4 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 10 + -2g = 4 + 2g + -2g Combine like terms: 2g + -2g = 0 10 + -2g = 4 + 0 10 + -2g = 4 Add '-10' to each side of the equation. 10 + -10 + -2g = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -2g = 4 + -10 -2g = 4 + -10 Combine like terms: 4 + -10 = -6 -2g = -6 Divide each side by '-2'. g = 3 Simplifying g = 3
| 4/3*3.14*(10)(10)(10) | | 4/3*3.14*(2)(2)(2) | | 2j-5=3 | | 2timesx=-5 | | 4/3*3.14*(6)(6)(6) | | -8x-2=15x-2 | | 6+7x=-4+2 | | 11(y-2)3y=-7y+14 | | 4/3*3.14*(24)(24)(24) | | (x+4)*(x+k)=x*x+x-12 | | x^5/2-16x^1/2 | | x(x-19)=120 | | 8xyz=25 | | 6x^4-45x^3-24x^2=0 | | z=10.2 | | 38-4x=6-8x | | -4x+7y=8 | | 4/3*3.14*(7)(7)(7) | | (x+4)(x+2)=8 | | 1/2(8n-2)=16-30 | | 2(5x+1)=9x+10 | | 5x+24=63 | | 25.1+1.84= | | 4/3*3.14*(12)(12)(12) | | 4(u-6)-7u=-21 | | 6x+10x=-12+x | | x(8x+2)=3x^2-6x+21 | | (7-x)(-4-x)=2-4x | | 3e=1/2 | | 12y-16=8 | | y=7.4-.44 | | -3.5x+18=-36 |